Os animais do Brasil nas Obras de Pierre Belon (1517‑1564) - Dante Martins Teixeira; Nelson Papavero (Arquivos de Zoologia, 2014)
The importance of Pierre Belon (1517‑1564) to Comparative Biology and his famous journey to the East have overshadowed his observations about the New World fauna, which up to now remained almost unnoticed. However, Belon may be lined up among the first natural sciences’ specialists in the Renaissance to describe specimens of the Brazilian fauna, preceding Conrad Gesner and even the testimony of chroniclers such as Hans Staden, André Thevet and Jean de Léry. Out of the ten titles published by Belon along his 47 years of life, six are relevant from that viewpoint, including the books related to his journey to the East and three zoological treatises. Belon alludes to at least eight representatives of the Brazilian fauna (molluscs, fishes, birds and mammals), foremost among them an armadillo (Dasypus sp.) observed by him in the markets of Constantinople. Aside from corroborating the impressive traffic of Neotropical products exhisting in the 16th century, as well as the noticeable interest shown by the Ottoman Empire in the New World, Belon’s texts bear witness, in an eloquent way, to the strong French presence in the Brazilian coast during the first half of the 16th century.